PENGELOLAAN SAYUR MAYOR DALAM PEMBUATAN PUPUK KOMPOS PADA MASYARAKAT DI JORONG GUNUNG NAGARI TANJUNG ALAM KABUPATEN TANAH DATAR - Vini Wela Septiana; Pori Susanti; Safriadi Safriadi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2020)
This activity was carried out in Tanjuang Alam village Tanjung Baru Sub district, Tanah Datar District. The analysis departs from the lack of public knowledge about the importance of managing and utilizing primary vegetables into compost—utilization of Ammi household industrial waste. The purpose of community service activities is to provide new insights and knowledge to the Jorong Gunung community. The importance of managing and utilizing household waste as well as fruit or crop yields from fields. So that the plant can grow and develop properly. Circumstances around the house. Environmental beneficiaries as a source of learning, studies on household waste treatment. By making compost from significant vegetables. The vegetable major means vegetables that are no longer suitable for cooking because the texture has begun to rot and can no longer be used optimally for cooking vegetables as usual. To utilize household waste and produce from a field, it is used as a compost that farmers can use for their plant fertility. The target of community service activities is aimed at residents who live in the Jorong of Mount Nagari Tanjung Alam, especially local farmer groups. The implementation starts with the survey and observation in the field. Service to the community involves Thematic Work-Study Students of the University of Muhammadiyah, West Sumatra. In total, there are 30 groups. Specifically for group 1, the writer himself involved in becoming DPL was ten people from various faculties. This activity resulted in active participation from the community to participate in identifying potentials and ideas for developing yields and improving the quality of the fields they worked on and establishing partnerships with the Village Government and local farmer groups in the context of managing primary vegetables in composting fertilizer in the Jorong Gunung community Nagari Tanjung Alam Tanah Datar District.